2017
DOI: 10.1371/journal.pone.0184851
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of equine round pen training videos posted online: Differences between amateur and professional trainers

Abstract: Natural Horsemanship is popular among many amateur and professional trainers and as such, has been the subject of recent scientific enquiry. One method commonly adopted by Natural Horsemanship (NH) trainers is that of round pen training (RPT). RPT sessions are usually split into a series of bouts; each including two phases: chasing/flight and chasing offset/flight offset. However, NH training styles are heterogeneous. This study investigated online videos of RPT to explore the characteristics of RPT sessions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the context of this study, the stress treatment may have sensitised to the horse to the aversive characteristics of the learning task stimuli further increasing activity in the defensive neural network 95 , slowing their acquisition of the learning task. Kydd et al, 96 reported wide variability in the way this type of method is employed and that amateur trainers elicit more stress-like behaviours than professionals. The HRs reported here align with those reported in studies of professional trainers using this method 97 , 98 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this study, the stress treatment may have sensitised to the horse to the aversive characteristics of the learning task stimuli further increasing activity in the defensive neural network 95 , slowing their acquisition of the learning task. Kydd et al, 96 reported wide variability in the way this type of method is employed and that amateur trainers elicit more stress-like behaviours than professionals. The HRs reported here align with those reported in studies of professional trainers using this method 97 , 98 .…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used in this work is based on the work of Kydd et al [ 50 ], who extracted animal research data from videos available on the YouTube digital platform, as an attempt to promote research from pre-existing resources.…”
Section: Methodsmentioning
confidence: 99%
“…Even though humans have a lengthy and close history with horses, there are frequent gaps in the owner’s/trainer’s/caregiver’s understanding of ethology, horse behaviour, and indicators of welfare [ 7 , 8 , 12 , 13 , 14 , 15 , 16 , 17 ]. The science behind how animals learn, how they perceive the world around them, and the way they respond to that information, is poorly understood by many amateurs and professionals who work with horses [ 8 , 12 , 16 , 18 , 19 , 20 , 21 ]. In instances where an owner/trainer/caregiver does have appropriate theoretical knowledge, it still does not always translate into practical application [ 8 , 11 ].…”
Section: The Horse In Societymentioning
confidence: 99%
“…Whilst owners, riders, trainers, and caregivers frequently describe how important the relationship is between a horse and their human, the human–animal interactions (HAIs) provided are often negative experiences for the horse, with many common handling and training techniques focusing on achieving the human’s goal at the time, with limited consideration of the horse’s emotional experience [ 22 , 23 ]. Negative reinforcement and punishment-based approaches are common in horse training and handling, with the goal being to generate behaviours that the human desires, with little true choice to the horse, and limited reward for participation other than the relief from, or avoidance of, an aversive stimulus [ 11 , 12 ].…”
Section: The Horse In Societymentioning
confidence: 99%